Internal and External Factors Influencing Share Prices of Nepalese Commercial Banks - Bajracharya, Saurav Ratna; Sawagvudcharee, Ousanee (Nepalese Journal of Management Science and Research, 2019)
This study examines the factors that influenced the share prices of Nepalese commercial banks between 2006/07 to 2015/16. The evidences from the study suggests that internal factors such as earning per share, dividend per share and price earnings ratio had positive significant relationship with the market price per share. However, the external factor ‘inflation rate’ had negative significant relationship with the market price per share.